Islamic Economic Crisis: A Systematic Review Using Bibliometric Analysis - Sabiq Al Qital; Aam Slamet Rusydiana (Institut Agama Islam Negeri Ponorogo, 2022)
The financial crisis impacts the economy of developing countries. The existence of a financial crisis causes the economic growth of a country to decline. Islam has a perspective on the economic crisis issue. This research aims to find out and map research related to trends in the Islamic Economic Crisis published by leading journals from 1978 to 2022 and have been indexed by Scopus. Analysis of keyword trends, authors, and institutions. no one has used bibliometric analysis in this study. The data analyzed were 531 research publications using descriptive statistical methods and bibliometric analysis. The results show that the number of articles discussing the theme of the Islamic Economic Crisis has an increasing trend from year to year, along with the global economic crisis in 2008. the most prolific is Hassan M.K. Meanwhile, the country with the most famous writers and the most in Malaysia. Based on the bibliometric analysis, the leading causes of the financial crisis are; Natural Disasters, Political Instability, Social Instability, Faction Reserve Banking System, and Product Derivation. The research provides information for researchers who focus on research in the field of the Islamic Economic Crisis. In the end, this theme is possible to continue to develop.Krisis keuangan berdampak pada ekonomi negara-negara berkembang. Adanya krisis keuangan menyebabkan pertumbuhan ekonomi suatu negara menurun. Islam memiliki perspektif terhadap isu krisis ekonomi. Penelitian ini bertujuan untuk mengetahui dan memetakan penelitian terkait tren Krisis Ekonomi Islam yang diterbitkan oleh jurnal-jurnal terkemuka dari tahun 1978 hingga 2022 dan telah terindeks Scopus. Analisis tren kata kunci, penulis, dan institusi. Tidak ada yang menggunakan analisis bibliometrik dalam penelitian ini. Data yang dianalisis sebanyak 531 publikasi penelitian menggunakan metode statistik deskriptif dan analisis bibliometrik. Hasil penelitian menunjukkan bahwa jumlah artikel yang membahas tema Krisis Ekonomi Islam memiliki tren yang meningkat dari tahun ke tahun, seiring dengan krisis ekonomi global pada tahun 2008. yang paling produktif adalah Hassan M.K. Sementara itu, negara dengan penulis paling terkenal dan terbanyak di Malaysia. Berdasarkan analisis bibliometrik, penyebab utama krisis keuangan adalah; Bencana alam, ketidakstabilan politik, ketidakstabilan sosial, sistem perbankan cadangan faksi, dan derivasi produk. Penelitian ini memberikan informasi bagi peneliti yang fokus pada penelitian di bidang Krisis Ekonomi Islam. Pada akhirnya, tema ini memungkinkan untuk terus berkembang.